Engineering Innovations Vol. 1 - Elena Gordo Odériz (Trans Tech Publications Ltd, 2022)
This journal volume presents results on the investigation of the characteristics of polycrystalline silicon thin film for solar cells and the development of the electrical model of an electrochemical cell with solid polymer electrolyte. Readers can also look at the results of the design and experimental investigation of cube satellite, pico hydro generator for the low energy consumption, and agricultural drone. The structural elements of these devices were produced by 3D printing technologies. The volume also presents the results of an experimental investigation of the thermal performance of the smart passive cooling roof system for residential buildings.